INVESTIGATING THE ROLE OF SUSTAINABLE ENGINEERING PRACTICES IN GREEN BUILDING DESIGN AND CONSTRUCTION - Aripin, Zaenal (Yayasan Kreatif Indonesia Emas, 2024)
Background:The construction industry is one of the most significant contributors to environmental degradation, with energy consumption, waste generation, and resource depletion being major concerns. In response to these challenges, sustainable engineering practices have emerged as essential for the development of green buildings. These buildings are designed to minimize environmental impact while promoting efficiency, health, and well-being for their occupants. Sustainable building practices include energy-efficient designs, renewable material usage, water conservation methods, and eco-friendly construction techniques. Aims:This paper aims to investigate the role of sustainable engineering practices in the design and construction of green buildings. It seeks to identify the critical aspects of sustainability in green building construction, assess the impact of these practices on energy use and environmental conservation, and analyze the integration of such practices into construction projects. Research Method:This research employs a mixed-methods approach, including a review of current literature on green building standards, case studies of successful green buildings, and expert interviews from professionals in the field. Data collection also involves analysis of sustainability metrics, such as energy efficiency, waste reduction, and material sourcing. Results and Conclusion:The findings indicate that sustainable engineering practices play a crucial role in reducing the environmental impact of buildings. Integrating renewable energy sources, utilizing low-impact construction materials, and optimizing resource management throughout the building's lifecycle contribute to significant environmental benefits. The conclusion highlights that the application of these practices not only promotes sustainability but also enhances the overall efficiency and economic viability of buildings. Contribution:This study contributes valuable insights into how sustainable engineering practices can be effectively integrated into green building design and construction. It offers actionable recommendations for industry stakeholders looking to adopt environmentally conscious construction methods.